2015
DOI: 10.1016/j.chemgeo.2015.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of African dust in soils in a montane tropical landscape in Puerto Rico

Abstract: Dust deposition provides rock-derived nutrients such as phosphorus (P) to terrestrial ecosystems. Over pedogenic timescales, as bedrock sources of P are depleted, dust sources of P may support productivity in certain ecosystems, but controls on the spatial variability of dust in montane forested systems are largely unknown. Here, we use neodymium (Nd) isotope ratios in 31 ridgetop surface soils to evaluate the spatial variability of dust contributions to soil across ~100 km2 in the Luquillo Mountains, Puerto R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 102 publications
2
16
0
Order By: Relevance
“…Likewise, the LREE enrichment in the surface layers of the regolith profiles (Fig. 4,7), although also somewhat affected by pedogenic processes, is consistent with input of Saharan dust, in agreement with previous studies that found dust to be an important source of trace metals and limiting nutrients to LCZO soils (Chapela Lara et al, 2017;McClintock et al, 2015;Pett-Ridge, 2009;Pett-Ridge et al, 2009b). In fact, atmospheric inputs allow LCZO soils to maintain relatively high cation stocks despite the neartotal depletion of the bedrock source .…”
Section: Decoupling Of Shallow and Deep Critical Zone Processessupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, the LREE enrichment in the surface layers of the regolith profiles (Fig. 4,7), although also somewhat affected by pedogenic processes, is consistent with input of Saharan dust, in agreement with previous studies that found dust to be an important source of trace metals and limiting nutrients to LCZO soils (Chapela Lara et al, 2017;McClintock et al, 2015;Pett-Ridge, 2009;Pett-Ridge et al, 2009b). In fact, atmospheric inputs allow LCZO soils to maintain relatively high cation stocks despite the neartotal depletion of the bedrock source .…”
Section: Decoupling Of Shallow and Deep Critical Zone Processessupporting
confidence: 91%
“…attributed to the greater total abundance of sorbing phases, such as clays and metal (hydr)oxides, in the volcaniclastic as compared to the granitic regolith McClintock et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Selected soil P fractions (total P, apatite P, labile P and occluded P at 0-20 cm depth) on ridgetops in Puerto Rico were not significantly controlled by erosion rates or soil residence time, however, erosion rates and residence times varied little between sites (McClintock et al, 2015). Data from slope transects in Brazil showed that young upper slope soils (Entisols) have higher apatite P and lower labile P concentrations than Inceptisols in mid and lower slope positions (Agbenin and Tiessen, 1994).…”
Section: Introductionmentioning
confidence: 87%
“…Uplift is typically associated with tectonic plate margins and a major control of erosion rates that are inversely related to soil residence times. Soil residence time in these studies is defined as the length of time that is required for soil material to be removed by erosion and replaced by soil production, and during which soil particles experience physical and biogeochemical conditions at the top of the weathering profile (Almond et al, 2007;Dere et al, 2013;McClintock et al, 2015). Compared to chronosequences developed in flat landforms, Amundson et al (2015) suggested that residence times for most hillslope soils in temperate climates give rise to neither N nor P limitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation